(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Physiologists need to perceive world scientific experience more widely, strive to include all the knowledge in the education system at universities for a wide perception and presentation of them through the prism of their own knowledge.